E-Commerce Development for the Digital Economy in Indonesia - Fashola, Ahmada Alif; Kusuma, Farid (Activa Yuris: Jurnal Hukum, 2024)
This research examines the development of e-commerce in the context of the digital economy in Indonesia. E-commerce has experienced rapid growth and has become the main driver of the digital transformation of the national economy. Using descriptive analysis methods and literature studies, this research examines the factors driving e-commerce growth, the challenges faced, and their impact on the Indonesian economy. The research results show that increasing internet penetration, growth in smartphone users, and changes in consumer behavior are the main catalysts for the development of e-commerce. However, uneven digital infrastructure, cyber security issues and the digital divide are still obstacles. E-commerce has been proven to contribute significantly to economic growth, job creation and financial inclusion. This research concludes that collaboration is needed between the government, industry players and society to optimize the potential of e-commerce in driving Indonesia's digital economy.